Gambaran Kejadian Ketuban Pecah Dini (KPD) di RSUP Prof. Dr. R.D. Kandou Manado Tahun 2018 - Syarwani, Teuku I.; Tendean, Hermie M. M.; Wantania, John J. E. (Universitas Sam Ratulangi, 2020)
Abstract: Premature rupture of membrane (PROM) is the rupture of the membrane before delivery. This study was aimed to determine the profile of PROM based on maternal age, parity, occupation, duration of PROM, type of delivery, gestational age, and perinatal outcomes. This was a descriptive and retrospective study. Samples were delivery women who had PROM at gestational age≥ 37 weeks and <37 weeks at Prof. Dr. R. D. Kandou Manado form January 1 to December 31, 2018. The results showed a total of 78 patients of PROM. Most patients were 20-34 years (65.39%), senior high school educated (71.80%), housewifery (69.23%), multiparity (58.87%), PROM ≥24 hours (65.38%), gestational age ≥37 weeks (85.90%), cesarean delivery (85.90%), and Apgar score of 7-10 (79.48%). In conclusion, PROM patients in 2018 were more common in age 20-34 years, senior high school educated, housewifery, multiparity, PROM ≥24 hours, gestational age ≥37 weeks, cesarean delivery, and a perinatal outcome of Apgar score of 7-10 (79.48%)Keywords: premature rupture of membrane Abstrak: Ketuban pecah dini (KPD) adalah keadaan pecahnya selaput ketuban sebelum persalinan. Penelitian ini bertujuan untuk mengetahui gambaran kejadian KPD berdasarkan usia ibu, paritas, pekerjaan, lamanya ketuban pecah, jenis persalinan, usia kehamilan, dan luaran perinatal. Jenis penelitian ialah deskriptif retrospektif. Sampelpenelitian ini ialah ibu bersalin yang mengalami KPD pada usia kehamilan ≥37 minggu dan <7 minggu di RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari -31 Desember 2018. Hasil penelitian mendapatkan total 78 kasus KPD yang terdiri dari ibu berusia 20-34 tahun (65,39%), pendidikan SMA (71,80%), IRT (69,23%), multipara (58,87%), ketuban pecah ≥24 jam (65,38%), usia kehamilan ≥37 minggu (85,90%), persalinan seksio sesarea (85,90%), dan Apgar score 7-10 (79,48%). Simpulan penelitian ini ialah kasus KPD pada tahun 2018 yang paling sering pada usia ibu 20-34 tahun, pendidikan SMA, IRT, multipara, ketuban pecah ≥24 jam, usia kehamilan ≥37 minggu, persalinan seksio sesarea, dan luaran perinatal Apgar score 7-10.Kata kunci: ketuban pecah dini